Intraneuronal sortilin aggregation relative to granulovacuolar degeneration, tau pathogenesis and sorfra plaque formation in human hippocampal formation - Jiang, Juan; Yang, Chen; Ai, Jia-Qi; Zhang, Qi-Lei; Cai, Xiao-Lu; Tu, Tian; Wan, Lily; Wang, Xiao-Sheng; Wang, Hui; Pan, Aihua; Manavis, Jim; Gai, Wei-Ping; et al. (Frontiers in Aging Neuroscience, 2022)
Extracellular β-amyloid (Aβ) deposition and intraneuronal phosphorylated-tau (pTau) accumulation are the hallmark lesions of Alzheimer’s disease (AD). Recently, “sorfra” plaques, named for the extracellular deposition of sortilin c-terminal fragments, are reported as a new AD-related proteopathy, which develop in the human cerebrum resembling the spatiotemporal trajectory of tauopathy. Here, we identified intraneuronal sortilin aggregation as a change related to the development of granulovacuolar degeneration (GVD), tauopathy, and sorfra plaques in the human hippocampal formation. Intraneuronal sortilin aggregation occurred as cytoplasmic inclusions among the pyramidal neurons, co-labeled by antibodies to the extracellular domain and intracellular C-terminal of sortilin. They existed infrequently in the brains of adults, while their density as quantified in the subiculum/CA1 areas increased in the brains from elderly lacking Aβ/pTau, with pTau (i.e., primary age-related tauopathy, PART cases), and with Aβ/pTau (probably/definitive AD, pAD/AD cases) pathologies. In PART and pAD/AD cases, the intraneuronal sortilin aggregates colocalized partially with various GVD markers including casein kinase 1 delta (Ck1δ) and charged multivesicular body protein 2B (CHMP2B). Single-cell densitometry established an inverse correlation between sortilin immunoreactivity and that of Ck1δ, CHMP2B, p62, and pTau among pyramidal neurons. In pAD/AD cases, the sortilin aggregates were reduced in density as moving from the subiculum to CA subregions, wherein sorfra plaques became fewer and absent. Taken together, we consider intraneuronal sortilin aggregation an aging/stress-related change implicating protein sorting deficit, which can activate protein clearance responses including via enhanced phosphorylation and hydrolysis, thereby promoting GVD, sorfra, and Tau pathogenesis, and ultimately, neuronal destruction and death.